Effect of tillage reduction on the productive behavior of cassava - Carvalho, Flávio Luiz Carpena; Souza, Luciano da Silva; Caldas, Ranulfo Corrêa; Mattos, Pedro Luiz Pires de (Pesquisa Agropecuaria Brasileira, 2014)
In a cassava (Manihot esculenta Crantz) experiment conducted in a yellow latossol, in Cruz das Almas, BA, Brazil, two tillage systems were compared: reduced tillage (soil preparation only in the planting rows) and conventional tillage (preparation of the whole area), the former being intercropped or not with a legume for green manure. The cassava cultivar BGM 001 ("aipim-bravo") planted in a 2.50 m x 0.50 m x 0.50 m double row spacing was harvested twelve months after planting. The experimental design was completely randomized, and years were taken as replications. The results after five years of continuous cultivation have shown no difference among the treatments for cassava root production, but the reduced tillage system gave a reduction of 65% to 75% on the costs of soil preparation, when compared to the conventional system.